The mediating effect of forgiveness on the relationship between spirituality and psychological well-being in adults with history of childhood bullying - Theodora, Michelle; Sahrani, Riana; Roswiyani, Roswiyani (Faculty of Psychology and Health - Universitas Islam Negeri Walisongo Semarang, 2023)
The long-term effects of childhood bullying on psychological well-being in adulthood have recently gained attention in research. This study examines the complex dynamics of the phenomenon by investigating the role of forgiveness as a mediator in the relationship between spirituality and psychological well-being among individuals who experienced bullying during their childhood. A purposive sample of 202 participants aged 19-40, who were bullied between the ages of 6-18, were recruited. The measurements used in the study included the Ryff Psychological Well-Being Scale (⍺ = .77) to measure psychological well-being; the Heartland Forgiveness Scale (⍺ = .82) to measure forgiveness; the Daily Spiritual Experiences Scale (⍺ = .94) to measure the spirituality of the participants; and the Olweus Bully/Victim Questionnaire (⍺ = .71) as a screening tool to confirm participants' experiences of bullying. Through mediation regression analysis with 5000 bootstrap samples using Macro PROCESS by Hayes, forgiveness emerged as a significant full mediator (β = .318, p < .05, 95% CI: .212, .438). The study provides evidence that forgiveness enhances psychological well-being, suggesting that implementing a forgiveness program could reduce the long-term effect of childhood bullying.